2017
DOI: 10.1002/micr.30146
|View full text |Cite
|
Sign up to set email alerts
|

The impact of resident involvement in breast reconstruction surgery outcomes by modality: An analysis of 4,500 cases

Abstract: Resident involvement is safe and effective across implant, free flap, LD, and TRAM based methods of breast reconstruction with similar major and wound complication rates. Participation of trainees in these surgical cases is imperative for future patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…A study by Zhang et al 33 examined the outcomes of resident-led microvascular reconstruction. 46 In comparison to the study by Jubbal et al 47 that examined the National Surgical Quality Improvement Program database for resident-assisted microsurgical reconstruction, Cho et al 46 reported a higher overall flap success rate (95.5% versus 93.6%) than the previous study and lower flap take back (7.0% versus 17.6%) in the resident-led cases. 46 , 47 However, the average operative time was slightly longer (525 versus 519 minutes).…”
Section: Microsurgery Training Modelsmentioning
confidence: 90%
“…A study by Zhang et al 33 examined the outcomes of resident-led microvascular reconstruction. 46 In comparison to the study by Jubbal et al 47 that examined the National Surgical Quality Improvement Program database for resident-assisted microsurgical reconstruction, Cho et al 46 reported a higher overall flap success rate (95.5% versus 93.6%) than the previous study and lower flap take back (7.0% versus 17.6%) in the resident-led cases. 46 , 47 However, the average operative time was slightly longer (525 versus 519 minutes).…”
Section: Microsurgery Training Modelsmentioning
confidence: 90%
“…The data include patient characteristics, postoperative complications, reoperations, readmissions with associated diagnoses, and time to event in days. The NSQIP dataset has been previously validated (Sellers et al, 2013), and has been used to evaluate outcomes for multiple microsurgical procedures (Bydon et al, 2014;Dasenbrock et al, 2015;Garg, Merrell, Hillstrom, & Wolfe, 2011;Jubbal, Echo, Spiegel, & Izaddoost, 2017;Jubbal, Zavlin, & Suliman, 2017;Mlodinow, Ver Halen, Rambachan, Gaido, & Kim, 2013). Our Institutional Review Board has exempted the NSQIP database from review.…”
Section: P a Ti E Nt S A Nd M E Th Odsmentioning
confidence: 99%
“…Whether this is a result of acquired course knowledge and skills, emotional bolstering of low-risk simulation, or other uncharacterized effects is unclear. Responses from a survey by Rostom and Lam given to 27 Scottish microsurgeons suggest that basic microsurgical skills (defined by them as vessel preparation, vessel anastomosis, muscle flap raising, and flap/donor site selection) should take between three to six (3)(4)(5)(6), and no more than nine (9), months of regular practice to achieve. 33 While microsurgical competency is obviously grounded in repetition and experience, with some suggesting training should even begin at the PGY-1 level, 34 courses such as this may serve as quarterly or biannual educational events intended to familiarize and boost trainees' comfort and confidence with microsurgical operations, and serve as a supplement to a solid foundation to what can be learned in the operating room.…”
Section: Operative Domainsmentioning
confidence: 99%
“…The extent to which traditional "Halstedian" apprenticeship experiences efficiently and consistently confers microsurgical competency for future independent practice remains unclear. [2][3][4] Resident work hour restrictions and a focus on quantifiable health outcomes have prompted the development of alternative, more systematic methods for teaching and assessing microsurgical techniques, such as surgical simulation. Simulation has the potential to enhance resident education, and impart technical proficiency in performing microsurgical anastomoses, particularly when used within a curriculum that incorporates didactic and practical components.…”
mentioning
confidence: 99%